Prevalence and Risk Factors of Post-traumatic Stress Disorder Symptoms in Students Aged 8–18 in Wuhan, China 6 Months After the Control of COVID-19 - Chen, Yue; Zhu, Zhuohong; Lei, Fei; Lei, Shulan; Chen, Jing (Frontiers in Psychology, 2021)
Objectives: To explore the prevalence of post-traumatic stress disorder (PTSD) symptoms and the factors influencing mental health symptoms in students aged 8–18 in Wuhan, China at 6 months after the COVID-19 pandemic was controlled. Methods: Questionnaires were distributed to students aged 8–18 in Wuhan through an online platform from September to October 2020, and 15,993 valid surveys were returned, resulting in a response rate of 75.4%. The data related to symptoms of PTSD, anxiety, depression, stress and psychological inflexibility levels, as well as demographic information about the population. Hierarchical multiple regression analyses were performed to examine the predictive effects. Results: In total, 11.5% of the students met the criteria for clinically concerning PTSD symptoms. Psychological inflexibility was associated with PTSD symptoms, depression, anxiety and stress symptoms (β = 0.45, 0.63, 0.65 and 0.69, respectively, with ΔR2= 0.16, 0.32, 0.34 and 0.39, respectively, p < 0.001) in children and adolescents. Conclusions: This study investigated the impacts of COVID-19 on the mental health status among students aged 8–18 in Wuhan. Even at 6 months after the outbreak was brought under control, some students were still affected. Psychological inflexibility was correlated with psychological symptoms in students. Therefore, methods to reduce psychological inflexibility may help improve the mental health states of students as part of psychological interventions.